2022
DOI: 10.3389/fmicb.2022.842893
|View full text |Cite
|
Sign up to set email alerts
|

Mycorrhizosphere Bacteria, Rahnella sp. HPDA25, Promotes the Growth of Armillaria gallica and Its Parasitic Host Gastrodia elata

Abstract: Gastrodia elata is an entirely heterotrophic plant, the growth of which is completely reliant on Armillaria gallica, an orchid mycorrhizal fungus. To avoid damaging ecosystems, G. elata cultivation is shifting from woodland to farmland. However, whether the microbial community structure remains stable during this conversation is unknown. Here, we cultivated G. elata in woodland or farmland and found that woodland-cultivated G. elata produced a greater yield and larger tuber size. The relative abundance of Rahn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 58 publications
0
11
0
Order By: Relevance
“…[42], which has different effects on the yield of G. elata Bl. [23]. After multiple generations of Armillaria, its activity and ability to provide nutrients decreased, thus resulting in a decrease in G. elata Bl.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[42], which has different effects on the yield of G. elata Bl. [23]. After multiple generations of Armillaria, its activity and ability to provide nutrients decreased, thus resulting in a decrease in G. elata Bl.…”
Section: Discussionmentioning
confidence: 99%
“…Seven phylogenetic branches can coexist with G. elata Bl. [21][22][23][24][25][26]. New Armillaria species in China are constantly being discovered.…”
Section: Introductionmentioning
confidence: 99%
“…Many bacteria found around plant roots (rhizosphere and/or mycorrhizosphere) have the ability to promote plant growth and are therefore known as plant growth-promoting bacteria (PGPB) ( Sessitsch et al, 2010 ; Liu et al, 2022 ). Few studies have reported the ability of PGPB to promote plant growth and its antagonistic potential against a variety of fungal pathogens.…”
Section: Discussionmentioning
confidence: 99%
“…Genomic DNA of the isolate was extracted according to the method of Welington et al ( Araujo et al, 2002 ). The 16S rRNA gene was amplified by PCR using a pair of universal primers, 27F (5′-CAGAGTTTGATCCTGGCT-3′) and 1492R (5′-AGGAGGTGATCCAGCCGCA-3′), as previous described ( Baik et al, 2008 ; Liu et al, 2022 ). The DNA gyrase subunit B ( gyrB ) gene was amplified with primers up-1 (5′-GAAGT CATCATGACCGTTCTGCAYGCNGGNGGNAARTTYGA-3′) and up-2r (5′-AGCAGGATACGGATGTGCGAGCCRTCNACR TCNGCRTCNGTCAT-3′) ( Yamamoto and Harayama, 1995 ; Duan et al, 2021 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation